Electrode Mass Loading Effects on Different Piezoelectric Substrates for Saw Delay Lines: A Comparative FEM Analysis - Sheeja P. George; Johney Issac; Jacob Philip (Archives of Acoustics, 2022)
Several modelling techniques are currently available to analyse the efficiency of inter-digital transducers (IDTs) fabricated on piezoelectric substrates for producing surface acoustic wave (SAW) devices. Impulse response method, equivalent circuit method, coupling of modes, transmission matrix method, and numerical techniques are some of the popular ones for this. Numerical techniques permit modelling to be carried out with any number of finger electrode pairs with required boundary conditions on any material of interest. In this work, we describe numerical modelling of SAW devices using ANSYS to analyse the effect of mass loading, a major secondary effect of IDTs on the performance of SAW devices. The electrode thickness of the IDT influences the resonance frequency of the SAW delay line. The analysis has been carried out for different electrode materials, aluminium, copper, and gold, for different substrate materials, barium titanate (BaTiO3), X-Y lithium niobate (LiNbO3), lithium tantalate (LiTaO3), and the naturally available quartz. The results are presented and discussed.